2010
DOI: 10.3892/ol_00000096
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-emodin, an anthraquinone, in vitro inhibits proliferation and induces apoptosis in human colon carcinoma cells

Abstract: Abstract. The present study aimed to investigate the anticancer effect of aloe-emodin, an anthraquinone compound present in the leaves of Aloe vera, on two human colon carcinoma cell lines, DLD-1 and WiDr. Colon carcinoma cells were treated with various concentrations of aloe-emodin for different durations. Cell viability was measured by sodium 3'-[1-(phenylamino-carbonyl)-3,4-tetrazolium]-bis(4-methoxy-6-nitro)benzene-sulfonic acid hydrate assay. DNA fragmentation was analyzed by agarose gel electrophoresis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
0
39
1
Order By: Relevance
“…This could be the reason for the lack of activation of caspase-3 in our experiment. There is also an issue of the elevated IC 50 values (150-220 mol/l) observed by Lin et al [11] when compared to the IC 50 of ϳ 25 mol/l observed in our study. This could be due to the differences in the percentage of FBS in the medium used for the analysis (10 vs. 2.5%).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…This could be the reason for the lack of activation of caspase-3 in our experiment. There is also an issue of the elevated IC 50 values (150-220 mol/l) observed by Lin et al [11] when compared to the IC 50 of ϳ 25 mol/l observed in our study. This could be due to the differences in the percentage of FBS in the medium used for the analysis (10 vs. 2.5%).…”
Section: Discussioncontrasting
confidence: 46%
“…However, in our study we did not observe caspase-3 activation in response to treatment with AE. It is important to note that the concentration used by Lin et al [11] was 370 mol/l, compared to the much lower concentration used by us mol/l). This could be the reason for the lack of activation of caspase-3 in our experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe emodin caused the release of apoptosis-inducing factor and cytochrome c from mitochondria, followed by activation of caspase-3 leading to DNA fragmentation, nuclear shrinkage and apoptosis. In addition, exposure of colon carcinoma cells to aloe emodin suppressed the casein kinase II activity in a time-dependent manner and was accompanied by a reduced phosphorylation of Bid, a downstream substrate of casein kinase II activity, the release of apoptosis-inducing factor and cytochrome c, and the caspase-3 activation are involved in aloe emodin-mediated apoptosis in colon carcinoma cells [30] . Moreover, differentiation of surviving cells toward the astrocytic lineage was confirmed by typical morphological changes and increased expression of glial fibrillary acidic protein (GFAP).…”
Section: In Vitro and Animal Studies Of Aloin And Aloe Emodinmentioning
confidence: 93%
“…For example, curcumin, isolated from the rhizome of Curcuma longa, demonstrates antioxidant abilities in vivo (17). Emodin, another natural anthraquinone, demonstrates protective or ameliorative effects against inflammation or oxidative stress-associated diseases (18,19). The aim of the present study is to assess the ability of emodin to alleviate the oxidative stress induced by cisplatin, and the results may elucidate the benefits of combined chemotherapy using emodin and cisplatin.…”
Section: Introductionmentioning
confidence: 99%